Studi Kasus: Optimalisasi Implementasi Pencegahan Risiko Jatuh Pada Pasien Di RS Wilayah Kota Depok Dengan Menggunakan Tiga Tahapan Perubahan Lewins - Pinandhika Jayawisastra (Politeknik Karya Husada, 2023)
Preventing the risk of falls is important in the process of implementing patient safety in hospitals. The consequences if an injury occurs from a fall will increase the patient's morbidity rate, prolong the length of stay and will be detrimental to the patient and the hospital. Although the prevalence of injuries due to falls is high, this incident can be prevented by using an initial assessment of the patient's risk of falling. Where research shows that almost 33% of patient falls during hospitalization can be prevented by managing the patient's fall threat factors as well as managing the environment and care process. Objective: This case report aims to describe the implementation of planned changes in optimizing the implementation of fall risk prevention. Method: The method used is a case report. Data collection uses interviews, questionnaires and field observations. The results of data exploration are then analyzed using SWOT (strengths, weaknesses, opportunities, threats) and fishbone diagrams, then formulating a plan of action (PoA), followed by implementation and evaluation. Results: Implementation results were not optimal because it was necessary to evaluate fall risk guidelines, regular supervision programs and carry out clinical audits or case reflection discussions related to fall risk prevention. Recommendation: Lewin's theory of change approach can be continued by hospital management as a form of developing quality services.